Relationship between Knowledge about Hypertension and Adherence to Taking Medication in the Elderly at the Nanggeleng Health Center, City - Amelia, Rini; Hadiyanto, Hendri; Utami, Tri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
This study aimed to analyze the relationship between knowledge about hypertension and adherence to taking medication in the elderly at Puskesmas Nanggeleng, Sukabumi City. This analytic observational study with a cross-sectional design involved 74 elderly people diagnosed with hypertension. Data were collected using a questionnaire that included demographic information, knowledge about hypertension, and medication adherence based on MMAS-8. Analysis was conducted using chi-square test with significant results (p-value 0.002 <0.05), indicating a positive relationship between hypertension knowledge and medication adherence. The majority of respondents (93.2%) had a good level of knowledge, while 86.5% showed high compliance in taking medication. Educational factors, especially the high school level of the majority of respondents (40.5%), play a significant role in improving knowledge and compliance. Family support is also an important factor in ensuring medication adherence. The results of this study emphasize the importance of health education to increase elderly knowledge about hypertension, so as to encourage adherence to treatment. The role of nurses as health educators is crucial in this process. This study makes an important contribution in identifying factors that influence the successful management of hypertension in the elderly, and suggests improving educational programs that involve families to encourage treatment adherence.